PENGARUH PERSON - ORGANIZATION FIT TERHADAP KOMITMEN ORGANISASI DAN KINERJA PERAWAT PELAKSANA MELALUI VARIABEL KARAKTERISTIK INDIVIDU DI RUMAH SAKIT X KUPANG - Veronika Papo Bage; Asnet Leo Bunga (NHM PRESS, 2023)
Person-organization fit is developed by many strategic management practitioners to analyze the influence on various variables in improving the quality of service in an organization. This study aims to examine and identify the influence of the person-organization fit on organizational commitment and the performance of implementing nurses through the characteristics of individuals in Hospital X, so that it has implications for improving the quality of hospital services, especially the quality of nursing services. This study uses a parallel mixed method convergent research design. Simple random sampling was taken by 200 respondents and 17 implementing nurses at X Kupang Hospital. Analysis of the data using Structural Equation Model (SEM) obtained CR ≥ 1.967 and p ≤ 0.05 then the person-organization fit with significant and positive influence on individual characteristics, the person-organization fit has a significant and positive influence on organizational commitment, organization fit has a significant and positive influence on the performance of nurses, person-organization fit has a significant and positive effect on organizational commitment through individual characteristics and commitment of organization-organization has a significant and positive effect on nurse performance. C.R -0.166 ≤ 1.967 and p 0.868 ≥ 0.05, the hypothesis was rejected so that there was no influence between person organization fit and nurse performance through individual characteristics. The results of qualitative research through the opinion of informants stated that individual values are in accordance with the values of the organization but the organization has not been able to empower the characteristics of the implementing nurse so that it becomes an opportunity for the organization to increase the commitment and performance of nurses. This provides an illustration that the relationship between relational, leadership, and employee relations with the organization has not been optimal. The application of person-organization fit needs to be a concern to be implemented comprehensively in order to create conformity of personal values and organizational values in order to achieve organizational goals.